(untitled) (Applied Biological Research, 2014)
The present study was conducted in 250 healthy dogs (120 females and 130 male) to assess vertebral heart size (VHS) in various the breeds and sex. The radiographic measurements recorded were right lateral VHS, left lateral VHS, dorsoventral VHS and cardiothoracic ratio CTR. The mean VHS established were RL (10.21 ± 0.10) LL (9.93 ± 0.14) and DV (10.09 ± 0.13) for Labrador, RL (10.24 ± 0.35) LL (10.03 ± 0.27) and DV (10.30 ± 0.42) for German Shepherd, RL (9.63 ± 0.23) LL (9.46 ± 0.39) and DV (9.73 ± 0.35) for Indian Spitz, RL (10.09 ± 0.22) LL (9.53 ± 0.33) and DV (10.03 ± 0.34) for Pug and RL (9.59 ± 0.31) LL (9.39 ± 0.45) and DV (9.42 ± 0.31) for non-descript native breeds. On RL and LL views, the Labrador and German Shepherd had significantly higher and native non-descript dogs had the lowest mean VHS measurements than other breeds. The findings reflect it is imperative to consider the breed and the side of radiographic view during evaluation of heart size based on thoracic radiographs.